Malignant adenomyoepithelioma of the breast - Kazuki Moro; Eiko Sakata; Asa Nakahara; Hideki Hashidate; Emmanuel Gabriel; Haruhiko Makino (Surgical Case Reports, 2020)
Abstract Background Adenomyoepithelioma (AME) of the breast is a very rare tumor and is generally considered to be benign. However, some show malignant transformation, which results in local recurrences or distant metastases. The morphological features of AME that might predict malignant potential have not been elucidated. Moreover, there is also no established multidisciplinary treatment for malignant AME aside from complete excision at an early stage. Case presentation A 64-year-old female diagnosed with AME of the left breast underwent lumpectomy. The surgical margins were negative. Six months after the operation, however, malignant AME recurred locally in the left breast. MRI showed multiple masses, which invaded the skin. A left mastectomy with axillary lymph node dissection was performed. Additional areas of AME were found in about one third of the entire breast. Eight months after the mastectomy, lung metastases were detected. She underwent chemotherapy with fluorouracil, epirubicin, and cyclophosphamide (FEC) for 9 cycles with little response. Lung metastasectomy was performed. Nine months after lung metastasectomy, the metastases were widespread to the brain, heart, and kidney; she subsequently died 2 months later. Conclusions Malignant AME has various morphological features, and in this report, we characterize new findings from both imaging and pathology/autopsy. Malignant potency is related to the tumor size, tumor appearance, and mitoses, even if only a few. Given that ductal spread is one of the morphological features of malignant AME, it is of paramount importance to assess the surgical margins.